Intervention on the Leaning Tower bell of Pisa: Between integrations and disengagement - Cruz-Ramírez, Luis Carlos (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
There are numerous technical solutions to intervention of heritage buildings that are useful to avoid or reduce degradation. Although these solutions have satisfactory experiences, they are not a guarantee to generalize them. To explain this curious fact, this study of the interventions was carried out in the course of history in the Bell Tower of the Cathedral of Pisa. This emblematic building has experienced differential settlements since its construction, generating its inclination for what is internationally known. During course of its existence, it has been a scenario of different types of interventions, mostly integrations and releases. A systematic review is presented on the different and most representative intervention actions, to know how these have influenced the variation of its state of degradation. Not all actions implemented were successful. Controlled on-site experimentation, with scale models, has so far been the safest way to intervention.